A Nyugat-dunántúli régió átalakuló élelmiszeripara esettanulmányok tükrében - Szabó, Sándor; Stárics, Roland; Vidéki, Imre (Jelenkori Társadalmi és Gazdasági Folyamatok, 2009)
Western-Transdanubia having a good quality agricultural potenciáis. After the democratic transformation it was a significance change in the region's industrial structure, of course in the the food processing industry as well. This article presents case studies about companies and small and middle enterprises from food processing industry. There are differences between developmental ways. Zalahús after a prosperous 10 years went benkrupt. The small enterprise called Bognár Szörp went to bankrupt fortuitously. Changing possessor could taking a company a developmental or a reducing way like the exemplars of Soproni Sörgyár or Győri Keksz- és Ostyagyár. One good plan, and innovation can lift an enterprise to a higher economical level as it happend with Lipóti Pékség. This small bakery had started to built a chain of shops and making good expansion plans.